Proactive approaches to the Mediterranean AgroCities - Gausa Navarro, Manuel; Canessa, Nicola Valentino; Tucci, Giorgia (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The evolution of the urban-territorial city and of our occupied environments produced, during the last decades, in Europe in a general way and in Italy in a specific way, a combination of matters regarding the relations City-Nature, City-Nature-Landscape and a change of prespective between the urban, physical and social dimension and the largest agricultural-landscape and agricultural-environmental system in the context within which the city redefines and develops itself. This change of prespective stabilized and manifested itself with the increasing awareness of the need that agricultural and forestry spaces must develop a plural, structural, articulate and functional role; a role within which various knowledges and regulations, various norms and sections of public policies are combined. Overcoming the opposition city-country, within which the suburban areas play a vital and active role - with its center within a productive and creator function of complex value - a new model of integrated approach towards territorial policies and the geo-urban project is needed, able to adequately represents the different applications within the territory. This kind of approach focus on a matter that, from the planning point of view appears unavoidable and that refers to the need of integration between territorial and political planning and rural development plans that combine primary/tertiary activities and agricultural production.